1996
DOI: 10.1507/endocrj.43.39
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Immunoreactive Activin A Secretion from Cultured Rat Anterior Pituitary Cells.

Abstract: Abstract.Immunoreactive activin A (ir-activin A) release from cultured rat anterior pituitary cells was examined by measuring ir-activin A in culture medium by a specific radioimmunoassay. Ir-activin A release into the medium increased over 1-18 days, and reached a maximal level at 12-15 days. The basal levels of ir-activin A in the culture media were 0.70 ± 0.10 (mean ± SD), 1.30 ± 0.36 and 1.83 ± 0.44 ng/106 cells, when cultured for 6 days with 0, 2 and 10% fetal calf serum, respectively. LHRH induced an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…Although the mechanism remains unclear, this stimulatory effect of LHRH on ir-follistatin release may be mediated by pituitary activin. We also found that ir-activin A seretion is significantly enhanced by LHRH in cultured rat anterior pituitary cells [21]. Furthermore, DePaolo et al demonstrated that pituitary follistatin expression is enhanced after castration by the mediation of pituitary activin [22].…”
Section: Molecular Heterogeneity Of Follistatin In the Culture Mediumsupporting
confidence: 67%
See 1 more Smart Citation
“…Although the mechanism remains unclear, this stimulatory effect of LHRH on ir-follistatin release may be mediated by pituitary activin. We also found that ir-activin A seretion is significantly enhanced by LHRH in cultured rat anterior pituitary cells [21]. Furthermore, DePaolo et al demonstrated that pituitary follistatin expression is enhanced after castration by the mediation of pituitary activin [22].…”
Section: Molecular Heterogeneity Of Follistatin In the Culture Mediumsupporting
confidence: 67%
“…There has been no direct evidence for the presence of FSH receptor in the pituitary, but we recently demonstrated that pituitary activin A secretion is suppressed by the addition of FSH [21], implying the possiblity that FSH may also exert a form of direct regulation in the pituitary, but further investigation is necessary to prove this hypothesis.…”
Section: Molecular Heterogeneity Of Follistatin In the Culture Mediummentioning
confidence: 90%
“…This does not exclude the fact that GnRH plays a role in stimulating the high FSH concentrations due to the absence of negative feedback in barrows. From other species it is known that GnRH and activin interact (Liu et al, 1996;Shupnik and Weck, 1998;Gregory et al, 2005) so that high GnRH concentrations might be paralleled by elevated activin. Because activin in turn inhibits the synthesis and release of GH (Childs and Unabia, 1997), these effects might also explain lower GH levels in surgical castrates.…”
Section: Discussionmentioning
confidence: 99%
“…Originally isolated from the gonads, activin has been detected in the rat anterior pituitary (Meunier et al 1988, Roberts et al 1989, Bilezikjian et al 1993, Halvorson et al 1994, Liu et al 1996, where it may play an autocrine/ paracrine role in the regulation of anterior pituitary hormones (Corrigan et al 1991, Besecke et al 1996. Recent studies have demonstrated that it has specific stimulatory effects on follicle-stimulating hormone (FSH) gene expression in the pituitary and FSH secretion in culture but has no effect with regard to luteinizing hormone (LH) (Vale et al 1986, Ling et al 1986, Kitaoka et al 1987, Ying 1988.…”
Section: Introductionmentioning
confidence: 99%